Pemanfaatan Pekarangan Rumah Untuk Budidaya Sayuran Sebagai Alternatif Usaha Sampingan Di Desa Loa Janan Ulu Kecamatan Loa Janan Kabupaten Kutai Kartanegara - Nurfiza Widayati; Selly Swandari; Akbar Lufi Zulfikar; Indra Maulana; Swadia Gandhi Mahardika (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The use of home gardens for vegetable cultivation in Loa Janan Ulu Village reflects the community's efforts to develop sustainable side businesses. With limited land area in the home gardens, villagers use it efficiently to grow vegetables. This aims to meet family food needs, improve welfare, and create alternative livelihoods. Loa Janan Ulu Village, located in Kutai Kartanegara Regency, has good agricultural potential, but limited land encourages people to use home gardens as fertile fields for various types of vegetables. Cultivating vegetables in home gardens provides double benefits, namely providing a supply of fresh vegetables for daily consumption needs and generating potential additional income through the sale of the harvest. The use of organic and environmentally friendly farming methods is increasingly being implemented by the community, creating a sustainable agricultural system and maintaining the sustainability of the surrounding environment. In addition, vegetable cultivation activities in home gardens also have the potential to increase food security and reduce dependence on supplies from outside the region. With initiatives like this, the people of Loa Janan Ulu Village not only act as consumers, but also as local vegetable producers who can contribute to the development of the local economy. The local government can support this effort by providing agricultural training, access to markets, and other supporting facilities to increase the productivity and sustainability of vegetable cultivation businesses in home gardens. The delivery method used is face-to-face lectures and discussing case studies of preparing business plans in the agricultural sector by visiting the location of the farming business in managing home gardens into a place of business that has economic value directly in Loa Janan, then continued with discussions and questions and answers. The equipment used includes a laptop and a photo camera for taking documentation. The results of this community service activity are expected to increase the income of vegetable farmers and this business will continue to grow and become a business that provides the main income to farmers in Loa Janan Ulu Village, Loa Janan District, Kutai Kartanegara Regency. The results of this vegetable farming business will be sold to the local market and the demand for this vegetable production is very high because it is a complement to the staple food of the local community. With the material on developing vegetable farming businesses to utilize home gardens that has been delivered, it is hoped that PKM participants, namely vegetable farmers, will be able to manage their businesses well so that they get maximum turnover in the future.